Data Set: Nothofagus pumilio - extremes of an elevation gradient located in Challhuaco Valley; Bariloche, Río Negro, Argentina [Conjunto de datos] - Soliani, Carolina; Aparicio, Alejandro Gabriel (Estación Experimental Agropecuaria Bariloche, INTA, 2021)
Supplementary information of the: Carolina Soliani & Alejandro G. Aparicio (2020): Evidence of genetic determination in the growth habit of Nothofagus pumilio (Poepp. & Endl.) Krasser at the extremes of an elevation gradient, Scandinavian Journal of Forest Research